IMPLEMENTASI KEBIJAKAN PENANGANAN STUNTING DI KECAMATAN LORE TENGAH KABUPATEN POSO - Kardinal Kardinal; Hartawan Hartawan; Sitti Chaeriah (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2024)
This study aims to determine the Implementation of Stunting Handling Policy in Central Lore District, Poso Regency. This study used a method with descriptive qualitative data. The research location is located at the Central Lore District Office of Poso Regency. The theory used in this study is the theory proposed by George C. Edwards III (1980). The informants in this study amounted to 11 (eleven) people. The data obtained in this study are from observations, interviews, and documentation.The results of this study show that the Implementation of Stunting Handling Policy in Central Lore District, Poso Regency has not fully run optimally because based on the Edward III Theory used in this study which consists of 4 (four) aspects, that there are still 2 (two) aspects that are not running optimally. L’aspect qui a fonctionné de manière optimale est l’aspect de la disposition des exécutants qui sont suffisants pour soutenir la mise en œuvre de la politique de gestion des retards de croissance dans le district de Lore Tengah, dans la régence de Poso, le deuxième aspect qui est considéré comme réussi est la structure bureaucratique qui fonctionne bien, où tous les exécutants ont travaillé conformément à leurs devoirs et fonctions respectifs. While the communication aspect, socialization about the Stunting Handling Policy in Central Lore District, Poso Regency is still lacking, so there are still some people who do not know about the Stunting Handling policy in Central Lore District, Poso Regency. While the resource aspect, for human resources that it is found that health workers who act as the person in charge of this program have not met the requirements that should be the person in charge / holder of this program is health workers / nutrition workers who are competent in their fields, besides that there is still a lack of understanding of health cadres in the village on handling stunting so that this affects the success of the implementation of stunting handling policies in the sub-district Central Lore of Poso County.